2022
DOI: 10.1038/s41598-022-05112-2
|View full text |Cite
|
Sign up to set email alerts
|

An explainable machine learning-based clinical decision support system for prediction of gestational diabetes mellitus

Abstract: Gestational Diabetes Mellitus (GDM), a common pregnancy complication associated with many maternal and neonatal consequences, is increased in mothers with overweight and obesity. Interventions initiated early in pregnancy can reduce the rate of GDM in these women, however, untargeted interventions can be costly and time-consuming. We have developed an explainable machine learning-based clinical decision support system (CDSS) to identify at-risk women in need of targeted pregnancy intervention. Maternal charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…On the one hand, the telehealth and telemedicine adoption showed promised outcomes in medical error reduction [35] , and assertiveness in the medical conduct [36] , as well as using CDSS to help predict prognosis and assist clinicians in screening [37] become positive impacts to promptness response and resolve complex cases by consulting remotely specialized professionals. This scenario became positive when compared with traditional attendance approaches.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the telehealth and telemedicine adoption showed promised outcomes in medical error reduction [35] , and assertiveness in the medical conduct [36] , as well as using CDSS to help predict prognosis and assist clinicians in screening [37] become positive impacts to promptness response and resolve complex cases by consulting remotely specialized professionals. This scenario became positive when compared with traditional attendance approaches.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Besides the use of AI to enhance experiences of both clinicians and patients [33] in healthcare. Furthermore, the growth of AI explainable learning has made the AI understandable, providing explanations catered to humans, promoting transparency about the decisions and consequently reliability, [37] , [45] . Once the healthcare professionals and patients do not accept decisions without understanding and trusting the explanations, or at least how the decisions are made [46] .…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Additionally, it is based on a ML model that was built using a small sample size (due to the rarity of the disease) on an Irish population. As a result, our intent is to evaluate the CDSS on both healthcare professionals and patients in the future and to collect data from an EU cohort to examine a potential ethnic/cultural difference in QoL prediction, similarly to the study by Du et al [ 51 ]. This will allow us to expand the scope of our CDSS beyond the Irish population.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous studies have demonstrated tradeoffs associated with including different types and numbers of factors and different populations, as shown in Table 2. [11][12][13][14][15][16][17][18] For selecting factors in an AI model, one must consider incorporating numerous detailed laboratory and genetic data to improve AI accuracy or fewer data only available with routine prenatal care to improve clinical usability. For different populations, one must decide whether to use data only from high-risk populations to improve accuracy (but sacrifice generalizability) or nonselected populations to improve generalizability (but sacrifice accuracy).…”
Section: Technology Needed To Improve the Use Of Ai To Predict Gestat...mentioning
confidence: 99%
“…Additional studies are also needed in large multinational, diverse populations to further improve predictive ability and ensure there are no biases by race or other factors. 18,20 Table 1. Suggestions for Clinicians Who Are Developing and Using AI for Delivering Care.…”
Section: Technology Needed To Improve the Use Of Ai To Predict Gestat...mentioning
confidence: 99%